Black-Brown Solidarity : Racial Politics in the New Gulf South - Márquez, John D. (Book collections on Project MUSE., 2014)
A scholarly study of Black-Latino solidarity and coalition in response to a Latino population boom in the Gulf South.--description provided by publisher.